Intelligent classroom management system - Islam, Md. Nahal; Tabassum, Farah; Sarker, Gourab Kumar; Sen, Dhrubashish (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.